2022
DOI: 10.1021/accountsmr.2c00095
|View full text |Cite
|
Sign up to set email alerts
|

Insights on Carbon Neutrality by Photocatalytic Conversion of Small Molecules into Value-Added Chemicals or Fuels

Abstract: Metrics & MoreArticle Recommendations CONSPECTUS: Photocatalytic conversion of small molecules (including H 2 O, CO 2 , N 2 , CH 4 , and benzene) into value-added chemicals or fuels (e.g., H 2 , NH 3 , C 2 + , etc.) is a promising strategy to cope with both the worldwide increasing energy demand and greenhouse gas emission in both energy sectors and chemical industry, thus paving an effective way to carbon neutrality. On the other hand, compared with conventionally thermo-or electrocatalytic processes, photoac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 58 publications
(142 reference statements)
0
10
0
Order By: Relevance
“…These irregularities can either naturally manifest during the material growth or be intentionally introduced through post-treatment processes. 44,45 Due to their ease of introduction, defects have found extensive use in studies related to photocatalytic CO 2 conversion. Their functions, such as optimizing the separation of photogenerated charge carriers, expanding the range of light absorption, and providing abundant catalytic sites, have demonstrated their effectiveness in enhancing the process of photocatalytic CO 2 conversion.…”
Section: Strategies For Enhancing C−c Couplingmentioning
confidence: 99%
See 1 more Smart Citation
“…These irregularities can either naturally manifest during the material growth or be intentionally introduced through post-treatment processes. 44,45 Due to their ease of introduction, defects have found extensive use in studies related to photocatalytic CO 2 conversion. Their functions, such as optimizing the separation of photogenerated charge carriers, expanding the range of light absorption, and providing abundant catalytic sites, have demonstrated their effectiveness in enhancing the process of photocatalytic CO 2 conversion.…”
Section: Strategies For Enhancing C−c Couplingmentioning
confidence: 99%
“…Defects, in the context of materials, pertain to irregularities that occur within the crystal lattice of a material. These irregularities can either naturally manifest during the material growth or be intentionally introduced through post-treatment processes. , Due to their ease of introduction, defects have found extensive use in studies related to photocatalytic CO 2 conversion. Their functions, such as optimizing the separation of photogenerated charge carriers, expanding the range of light absorption, and providing abundant catalytic sites, have demonstrated their effectiveness in enhancing the process of photocatalytic CO 2 conversion. , Moreover, recent advancements have shown that defect engineering can also be employed to modulate the selectivity of products generated during photocatalytic CO 2 conversion .…”
Section: Strategies For Enhancing C–c Couplingmentioning
confidence: 99%
“…They can provide more opportunities for the separated electrons/holes to engage in subsequent photoreactions (Scheme 1) and promote energy conversion. 3,6 Among them, fullerenes can act as electron acceptor candidates to achieve stable and long-lived CSs. Represented by C 60 , fullerenes are unique gifts from the cosmic nebulae known as "Nano Prince".…”
Section: Introductionmentioning
confidence: 99%
“…Currently, driven by the energy crisis and environmental pollution, high-performance photoelectronic materials with donor (D) and acceptor (A) structures are increasingly favored by researchers to utilize solar energy and facilitate energy conversion fully. These materials are widely used in organic photovoltaics, photocatalysis, mimicking photosynthesis, photoluminescence materials, and other fields. Among these materials, the stable and long-lived charge-separation state (CSs) determines performance directly. They can provide more opportunities for the separated electrons/holes to engage in subsequent photoreactions (Scheme ) and promote energy conversion. , Among them, fullerenes can act as electron acceptor candidates to achieve stable and long-lived CSs.…”
Section: Introductionmentioning
confidence: 99%
“…Photocatalysis is a promising technology to simultaneously relieve worldwide energy crisis and environmental pollution issues, supplying an effective avenue to realize carbon neutrality. , Through photocatalysis reactions, different small molecules, such as H 2 O, N 2 , and CO 2 , can be converted to high-value-added chemicals with only the consumption of sustainable solar energy. Despite enormous prospects, current photocatalysis research faces the problem of low catalytic efficiency. During the photocatalytic reaction, the semiconductors are excited under solar irradiation to generate electron–hole pairs.…”
Section: Introductionmentioning
confidence: 99%